An efficient deep learning approach to predict heart failure from image data using ejection fraction - Tanvir, Nazmul Karim; Yeasin, MD. Nadim; MD. Mahmuduzzaman, Sarker; Ara, Jannat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.